Die Umsetzung der GloBE Rules (Pillar Two) in den USA - Schmidt, Nina (Young Academics: Internationales Steuerrecht, 2023)
About ten years ago, the OECD, together with the G20 countries, launched the BEPS project with the aim of adapting existing international tax structures to progressive globalisation. As a result or as part of this project, 139 countries have now participated in the development of an internationally agreed minimum tax system, the so-called GloBE rules ('Pillar Two'). The United States has played a crucial role in this development. Nina Schmidt examines whether and to what extent the US has or will implement the consensus solution for effective minimum taxation at the national level, and what the consequences might be if the US does not implement the GloBE Rules at the national level.